Long‐term outcome and recurrence of hepatitis B virus following liver transplantation from hepatitis B surface antigen‐positive donors in a Chinese population. Issue 12 (14th August 2018) - Wei, Lai; Chen, Dong; Zhang, Bo; Zhao, Yuanyuan; Liu, Bin; Shi, Huibo; Zeng, Fanjun; Ming, Changsheng; Jiang, Jipin; Du, Dunfeng; Chen, Zhishui
Summary: Due to the severe shortage of the donor pool in China, a large number of patients are waiting for a suitable liver, or even worse lose the opportunity of transplantation. Reasonable use of hepatitis B surface antigen‐positive (HBsAg‐positive) donors is one possible strategy to increase the donor pool but the long‐term outcome in a Chinese population is unknown. To evaluate the safety of using of HBsAg‐positive donor for liver transplantation, we set up a multicentric retrospective study from 1 January 2007 to 31 December 2012. A total of 8632 patients underwent liver transplantation during the period and 282 (2.97%) received a liver from a HBsAg‐positive donor. A total of 259 cases in both the case and control groups were matched. The incidence of postoperative liver dysfunction, early‐stage and long‐term complications and the 1‐, 3‐ and 5‐year patient survival (78.92% vs 85.65%, 60.41% vs 69.14%, 58.08% vs 69.14%, respectively) showed no difference between the two groups ( P value > 0.05). However, the 1‐, 3‐ and 5‐year HBV recurrence for patients received the HBsAg‐positive donor was higher compared with controls (5.85% vs 1.97%, 11.63% vs 4.46%, 17.94% vs 4.46%, respectively, P value = 0.016). Our results showed the use of HBsAg‐positive donors is feasible and postoperative antiviral therapy should be managed.